2015
DOI: 10.1002/ejp.774
|View full text |Cite
|
Sign up to set email alerts
|

Role of peripheral sigma‐1 receptors in ischaemic pain: Potential interactions with ASIC and P2X receptors

Abstract: Peripheral Sig-1Rs contribute to the induction of ischaemia-induced MA via facilitation of ASICs and P2X receptors. Thus, peripheral Sig-1Rs represent a novel therapeutic target for the treatment of ischaemic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…It was recently reported that the local administration of PRE-084 synergistically enhanced the mechanical allodynia induced by low pH (which activates acid-sensing ion channels) and α-β-methylene-ATP (an agonist of P2-purinoreceptors)23. These findings together with our results indicate that σ 1 agonism is able to promote to the development of mechanical allodynia after priming of the nociceptive system by several agents.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…It was recently reported that the local administration of PRE-084 synergistically enhanced the mechanical allodynia induced by low pH (which activates acid-sensing ion channels) and α-β-methylene-ATP (an agonist of P2-purinoreceptors)23. These findings together with our results indicate that σ 1 agonism is able to promote to the development of mechanical allodynia after priming of the nociceptive system by several agents.…”
Section: Discussionsupporting
confidence: 85%
“…It was previously reported that σ 1 receptor expression can increase in the spinal cord26 and in peripheral nervous tissues23 in chronic pain models, and this might influence the development of sensory hypersensitivity1323. Therefore, we also aimed to test whether chronic σ 1 activation by the selective σ 1 agonist PRE-084 is able to induce sensitization to mechanical stimuli per se or to promote mechanical hypersensitivity after the administration of capsaicin, and whether its effects are due to the altered expression of σ 1 receptors in key areas of the pain pathways in the central and peripheral nervous system.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…In fact, it has been suggested the importance of the endoneurial microenvironment and the maintenance of adequate perfusion in the selection of agents and design of clinical trials in diabetic neuropathy (Cameron and Cotter, 1994). Other authors have also proposed that the blockade of peripheral σ1R induced analgesic effect in ischemic pain (Kwon et al., 2016). The dual effect of σ1R antagonists could be interesting and more research in relation to that is needed to identify new potential levels of intervention for different neuropathies.…”
Section: Discussionmentioning
confidence: 99%